THE EFFECT OF FLIGHT OPERATION COMMERCIAL AND TECHNICAL DELAY ON ON-TIME PERFORMANCE OF PT GARUDA INDONESIA - Setiawan, Indra; Arianto, Bagus; Oktaviani, Reni Dian (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2018)
PT Garuda Indonesia is a state-owned enterprise that run business in commercial air transport industry. The purpose of this paper was to examine the effect of delay Flight Operation, Commercial, and Technical On On-time Performance. To obtain that purpose, writer used analysis method of Classic Assumption Test (Multicollinearity, Autocorrelation, Heteroscedasticity, Linearity), Simple Linear and Multivariate Linear regression, correlation coefficient, coefficient of determination, and hypothesis test. The analysis shown that all independent variable is obtained BLUE criteria and could be used as good estimator for next discussion. Multivariate regression equation is Y = 98,481 – 0,039X1 – 0,016X2 – 0,006X3 means that every increase of X1 (Flight Operation delay), X2 (Commercial delay), and X3 (Technical delay) will impact to the change of Y variable (On-time Performance) at the level of 0,039, 0,016, and 0,006 unit of count and at 98,481 intercept point. Correlation coefficient (r) at 0,846 represent strong correlation between variables. Coefficient of determination at 71,6%. From the hypothesis test, it shown that F result (26,910) >F Table (2,90), means that H0 is rejected and H1 is accepted, means there is a correlation between X1, X2, and X3 toward Y variable (On-time Performance) simultantly in PT Garuda Indonesia year2014-2016.